Respuesta :

Answer:

  3x +y -18 = 0

Step-by-step explanation:

The equation of the perpendicular line can be formed from the given equation by swapping the x- and y-coefficients, and negating one of them. The constant in the new equation will be the constant necessary to make the line pass through the given point.

__

swapped coefficients

  3x +y +c = 0 . . . . . now both coefficients are positive

new constant

We want c such that the equation is satisfied at the point (x, y) = (9, -9):

  3(9) +(-9) +c = 0

  27 -9 +c = 0

  c = -18

equation of perpendicular line

The equation of the desired line is ...

  3x +y -18 = 0

Ver imagen sqdancefan